Multidimensional Model of the ZPD as Tool of Analysis of the Child’s Cognitive-Personal Dynamics of Development While Overcoming Learning Difficulties (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
The main idea of the paper is based on L. S. Vygotsky’s concepts of ZPD and collaboration of teacher and student. The special process between teacher and student, organised in child’s zone of proximal development with using reﬂection and reﬂective questions as mail helping tools, leads to qualitative changes ﬁrstly in cognitive development of the student. Successes in learning activity create base for development of personal features. Thus, in such process, we may see strong connections between cognitive and personal developmental trajectories. Understanding of these connections gives an opportunity of mediative work with personal diÿculties of a child, opportunity to turn simple processes of learning into counseling work, e˙ecting all spheres of development.
Keywords: L. S. Vygotsky; ZPD; Collaboration between teacher and student; Tools